Inhibiting Factors of Pine Forest Tourism Management in Motilango Village, Tibawa District, Gorontalo Regency - Aisah Bint Yasin; Sofyan Alhadar; Yahya Antu (International Journal of Sustainable Applied Sciences, 2023)
This study aims to determine the Inhibiting Factors of Pine Forest Tourism Management in Motilango Village, Tibawa District, Gorontalo Regency. This study used a descriptive type of qualitative approach. With a research focus on Planning, Organizing, and Supervising. Where data collection is carried out through interviews, observation and documentation. The results of the study concluded that, planning in terms of pine forest tourism management has not been realized optimally and organizing has not been optimal because the form of organizing has not been maximally carried out because there is no coordination between the government and the community in developing pine forest tourism and management supervision has not been optimal because there is no form of village government support in terms of making the performance of pine forest tourism site administrators